PERLINDUNGAN HUKUM DALAM TRANSAKSI EKONOMI SYARIAH - Abd. Rahman Shaleh (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2021)
Islamic economic transactions today have become a necessity in conducting economic transactions. Be it through selling transactions, buying economic trade transactions and the like. This is in line with the life of the Islamic community in which the Shari'a is always embedded as a benchmark for obedience to religion as a way of life. Sharia economic principles must be accompanied by clear legal protection so that there is comfort in conducting sharia economic transactions. So there is legal protection that protects it if there are problems or legal disputes behind the day. This legal protection exists since syriah economic transactions are carried out and transacted, namely obedience to the legal principles that underlie them in sharia economic governance. Religious court laws and compilations of Islamic law have provided legal protection in sharia economic transactions. That is, obey what is being transacted and use the legal route of the religious court as a legal umbrella in sharia economic disputes.